EDUKASI MANAJEMEN HARIAN PERAWATAN LUKA DIABETES MELITUSDI BANGSAL MELATI BARAT RSUD dr.SOEHADI PRIJONEGORO SRAGEN - Denata Asri Martias Putri; Estu Pradhika; Iin Selviana Sari; Irma Mustika Sari; Kushariati Kushariati (Jurnal Padamu Negeri, 2026)
Diabetes mellitus is a chronic metabolic disease with an increasing prevalence worldwide, including in Indonesia. Leaflet-based and demonstration education for daily management of diabetic wound care has proven effective in improving patient knowledge and skills in Melati Barat Ward, RSUD dr Soehadi Prijonegoro Sragen. A significant improvement was observed from pre-test results (40% correct answers) to post-test results (87% correct answers). This intervention also helped patients develop a daily schedule supporting blood sugar control and accelerating wound healing, enhancing patient independence and reducing the risk of recurrent complications.